SISTEM PENDUKUNG KEPUTUSAN DALAM PROSES SELEKSI PERMOHONAN KREDIT DI BPR ARTHA PRIMA PERSADA JAMBI MENGGUNAKAN METODE AHP - Lisdarti - (JURNAL AKADEMIKA)
PT BPR Artha Prima Persada is one financial institution in Indonesia in the form of a bank that provides financial services using the principles of conventional banking. BPR PT Artha Prima Persada provide financial assistance in the form of credit payment/installment and have multiple systems, procedures and requirements that must be met by prospective borrowers. So in an effort to improve the profitability of the bank financing it needs to be done to keep the management of quality is maintained financing of troubled finance and risk of loss. For the sake of efficiency and effectiveness of work then making the right decision is needed. Thus, in determining the creditworthiness of borrowers PT BPR Artha Prima Persada there be some assessment criteria. This assessment is based on the analysis of qualitative analysis 5C (Character, Capital, Capacity, Condition of Economy, Collateral).The purpose of this study is to design, apply and develop a decision support system (DSS) that is able to give a decision to the credit worthiness of prospective customers. The method used in the decision support system is a method of AHP (Analytical Hierarchy Process).